IS GENOME PACKAGING IN SMALL PLANT VIRUSES ENERGY INDEPENDENT? - A. Mohanty; J. Kumar; T. Ranjan; R. R. Kumar; K. Rajani (Journal of Animal and Plant Sciences, 2023)
Genome packaging is a critical step during the viral maturation process. Viruses employ a distinct approach to package their genetic materials inside capsid: ranging from very simple strategy of nucleation of capsid proteins onto genome to complex segro-packasome machinery. The majority of small plant viruses, which falls under type I passive system, package their genome into stable virions in the cytoplasmic compartment, where chances of co-packaging of host RNA is very high, indicates viruses evolved the mechanism of selective and stringent packaging of their genomes. Recent discoveries of the unique ATPase fold in the capsid proteins of smaller plant viruses and their direct or indirect role during genome packaging have changed the perception about genome packaging in type I system. We feel that viruses of type I system have acquired unique and independent innovations for genome packaging over the course of evolution. The molecular interactions, intriguingly, cross-talk between capsid proteins and conserved signal sequence situated at the end of genome, plays an important role while viral genome packaging and translocation. Strategy utilized by smaller plant viruses for enhancement of selective genome packaging does not depend simply on nucleation of capsid proteins over genome but interestingly, configuration of viral genome, replicase, tRNA, viral encoded movement proteins are the other important key players that regulate genome packaging. The main aim of this review is to discuss and revisit the mechanism of genome packaging among viruses of agronomic importance. This study will be also useful for understanding the origin and evolution of viral genome packaging apparatuses and their roles in eukaryogenesis.
Keywords: Plant viruses; Viral genome packaging; Energy independent packaging system; Capsid protein; ATPase fold